Peran Media Animasi Dalam Meningkatkan Kemampuan Membaca Permulaan Siswa Kelas 1 Inpres Wolomarang - Benyamin - Regi (Jurnal SASAK : Desain Visual dan Komunikasi, 2022)
Abstract Animation Media has a very important role in improving the ability to read early in the 1st grade of SDI Wolomarang. This research aims to find out the extent to which an animation medium can be used and measure the development of reading skills in elementary class students. At an early age, students are more familiar with media that are visually more interesting and memorable than boring verbal presentations. This research uses quantitative research methods with data collection techniques including tests and observations, analyzed using the T-test test. From the results of the calculation of the T-test there is a calculation of 2,410 and t table with dk = 15 and a significant level = 0.05 is 1,753. it can be concluded that t calculate > ttabel (2,410>1,753) so that Ho is rejected and Ha is accepted. From these results, it can be seen that there is an influence on the use of animation media on the ability to read early in the 1st grade of Inpres Wolomarang Elementary School. Thus it can be concluded that the student's initial reading ability and first grade student learning outcomes changed in a better direction after using animation media in experimental classes.